Removal of non-specific serum inhibitors of haemagglutination of rubella virus by treatment with dodecylamine-gel. Issue 11 (November 1976) - Ho, W K; Shortridge, K F
Abstract : The suitability of using dodecylamine-gel for removing the serum non-antibody-like inhibitors of haemagglutination by rubella was studied. Compared with kaolin and MnCl2/heparin treatment this new procedure appears to have a higher specificity since it removes the non-antibody-like inhibitors from serum without affecting the immunoglobulin level significantly. The potential application of this procedure in routine serological analysis for rubella virus infection is discussed.